FROM WORDS TO ERRORS: ANALYZING LEXICAL CHALLENGES IN INSTAGRAM'S MACHINE TRANSLATION OF 'NYTIMES’ - Wiwekananda, I Putu Riky; Verayanti Utami, Ni Made (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2024)
In the current digital era, disseminating information via social media is very easy and quick, but this can also increase the spread of wrong and inaccurate information to the public caused by translation errors in automatic translations on social media. The main objectives of this research are 1. Identify the types of translation errors found in Instagram Machine Translation in Translating the Caption of the